Holy terrors Latin American women perform - Taylor, Diana 1950-; Costantino, Roselyn; Versényi, Adam; Stambaugh, Antonio; Stoklos, Denise; Muñoz, José; Watanabe, José 1946-2007; Scott, Lorna; Carson, Margaret; Feitlowitz, Marguerite; Cancio, Marlène; Villefañe, Miguel; et al. (Duke University Press, 2003)
Holy Terrors presents exemplary original work by fourteen of Latin America's foremost contemporary women theatre and performance artists. Many of the pieces-including one-act plays, manifestos, and lyrics-appear in English for the first time. From Griselda Gambaro, Argentina's most widely recognized playwright, to such renowned performers as Brazil's Denise Stoklos and Mexico's Jesusa Rodríguez, these women are involved in some of Latin America's most important aesthetic and political movements. Of varied racial and ethnic backgrounds, they come from across Latin America-Argentina, Brazil, Mexico, Chile, Colombia, Puerto Rico, Peru, and Cuba. This volume is generously illustrated with over seventy images. A number of the performance pieces are complemented by essays providing context and analysis.The performance pieces in Holy Terrors are powerful testimonies to the artists' political and personal struggles. These women confront patriarchy, racism, and repressive government regimes and challenge brutality and corruption through a variety of artistic genres. Several have formed theatre collectives-among them FOMMA (a Mayan women's theatre company in Chiapas) and El Teatro de la máscara in Colombia. Some draw from cabaret and 'frivolous' theatre traditions to create intense and humorous performances that challenge church and state. Engaging in self-mutilation and abandoning traditional dress, others use their bodies as the platforms on which to stage their defiant critiques of injustice. Holy Terrors is a unique English-language presentation of some of Latin America's fiercest, most provocative art.ContributorsSabina BermanTania BrugueraPetrona de la Cruz CruzDiamela EltitGriselda GambaroAstrid HadadTeresa HernándezRosa Luisa MárquezTeresa RalliDiana RaznovichJesusa RodríguezDenise StoklosKatia TiradoEma Villanueva